Black Bruin: The Biography of a Bear - Hawkes, Clarence, 1869-1954; Copeland, Charles, 1858-1929 (Salt Lake City, UT : Project Gutenberg, 2007)
"Black Bruin: The Biography of a Bear" by Clarence Hawkes is a narrative work likely written in the early 20th century. This book presents a fictional story about the life of a bear, particularly focusing on the journey of the titular character, Black Bruin, who navigates the challenges and adventures of both wilderness life and encounters with humans. The opening of this biography delves into a vivid introduction of a farm family experiencing a frightful encounter with a bear that breaks into their home on a snowy night, leading to the mysterious abduction of their baby. The narrative establishes the bear's strong, maternal instincts as it investigates the cradle of the sleeping child. The father$1 (Bs desperate attempt to retrieve his child sets the stage for a thrilling chase into the woods, revealing a blend of danger and humanity. This engaging blend of tension and whimsy promises to captivate readers, presenting the complexities of wildlife interactions and the bear's anthropomorphized characteristics throughout the story. (This is an automatically generated summary.)s
Release date is 2007-05-09
Produced by Al Haines
Keywords: Bears -- Juvenile fiction